PENGARUH PERTUMBUHAN PENDUDUK DAN TINGKAT UPAH MINIMUM TERHADAP KESEJAHTERAAN MASYARAKAT DI KOTA SURABAYA - Stevani, Jasmine Vernadya; Arief, Sjamsul (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2020)
This study aims to examine the effect of population growth and the minimum wage on people's welfare in the city of Surabaya. This study uses secondary data obtained from official websites such as the Central Bureau of Statistics of East Java Province, the Central Bureau of Statistics in Surabaya. and the type of data used in this study is the type of quantitative data. The analysis technique used is multiple linear regression analysis. The results of this study indicate that 1. Partially population growth and the minimum wage have a positive and significant effect on people's welfare with a significant value of the t-test of the population growth variable of 0.045 (less than 0.05) and for the significant value of the t-test of the minimum wage variable of 0.002. (less than 0.05). 2. Together (simultaneously) the effect of the application of population growth and the minimum wage has a positive and significant effect on the welfare of the people of Surabaya City as evidenced by the significance value of the F test of 0.002 which is smaller than 0.05